Inclusive Education for Students with Disabilities: Evidence-Based Practices, Frameworks, and Policy Directions - Dr. Vandana Singh Thakur; Manish Kumar Meena (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Inclusive education the practice of educating students with disabilities alongside their non-disabled peers in general education settings has become a central goal of special education policy and practice worldwide. This paper reviews the legal foundations, theoretical frameworks, and evidence-based instructional strategies that underpin effective special education services. It examines the continuum of educational placements required by the principle of the Least Restrictive Environment (LRE), the role of Multi-Tiered Systems of Support (MTSS) and Universal Design for Learning (UDL) in differentiating instruction, and the contribution of assistive technology to student access and independence. The paper also considers persistent barriers to inclusion, including resource constraints, attitudinal factors, and gaps in teacher preparation, and offers recommendations for strengthening collaborative, family-centered, and data-driven practice. The synthesis suggests that well-implemented inclusive models, supported by adequate training and resources, benefit both students with disabilities and their typically developing peers academically, socially, and emotionally.